Manajemen Kepemimpinan Kepala Sekolah dalam Meningkatkan Kinerja Guru Honorer - Fitria, Fitria; Fitria, Happy; Martha, Alfroki (Yayasan Sembilan Pemuda Indonesia, 2020)
This study aims to determine the description of the Principal's leadership management in SMP Muhammadiyah Prabumulih and has uses in various parties, both from the place of research and the authors themselves. In this study, the population is the principal, vice principal and honorary teacher consisting of 10 people, each of whom has different functions, qualities and characteristics. Collecting research data through three main sources, namely: direct observation (observation) document analysis, and interviews to get the principal's leadership score and the teacher's performance score. The data analysis technique used is descriptive qualitative analysis technique. These results indicate that: (1) the optimal form of leadership is played by the principal's role as a leader, manager, and motivator. (2) the obstacle faced by school principals when carrying out their duties is the performance of honorary work in this school has been running quite well even though some are still lacking discipline in attendance due to various reasons and interests.